2014
DOI: 10.1007/s11104-014-2028-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the critical period for waterlogging on yield and its components in wheat and barley

Abstract: Background and aims Crop tolerance to waterlogging depends on factors such as species sensitivity and the stage of development that waterlogging occurs. The aim of this study was to identify the critical period for waterlogging on grain yield and its components, when applied during different stages of crop development in wheat and barley. Methods Two experiments were carried out (E1: early sowing date, under greenhouse; E2: late sowing date, under natural conditions). Waterlogging was imposed during 15-20 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
143
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 52 publications
25
143
4
Order By: Relevance
“…Nevertheless, several other studies have demonstrated that waterlogging at the early phase of growth significantly reduced neither biomass nor yield of wheat because waterlogging occurring early in the crop cycle allowed plants to recover from stress by different mechanisms.,This would be related to the waterlogging duration and other factors. The duration of waterlogging in most previous studies were less than 20 days (Cannell et al, 1980;Jiang et al, 2008;de San Celedonio et al, 2014), but our study showed that after 35 d of waterlogging at different stages, the wheat was still alive and had some photosynthetic capacity. This was due to the soil texture of the experimental area.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Nevertheless, several other studies have demonstrated that waterlogging at the early phase of growth significantly reduced neither biomass nor yield of wheat because waterlogging occurring early in the crop cycle allowed plants to recover from stress by different mechanisms.,This would be related to the waterlogging duration and other factors. The duration of waterlogging in most previous studies were less than 20 days (Cannell et al, 1980;Jiang et al, 2008;de San Celedonio et al, 2014), but our study showed that after 35 d of waterlogging at different stages, the wheat was still alive and had some photosynthetic capacity. This was due to the soil texture of the experimental area.…”
Section: Discussioncontrasting
confidence: 68%
“…Several studies examined the critical period of waterlogging on wheat grain yield, suggesting that the reproductive stages was more adversely affected than the vegetative growth stages (Li et al, 2001;Setter and Waters, 2003). However, some studies have demonstrated that the period from the beginning of stem elongation to anthesis were most sensitive to waterlogging, in terms of yield penalties (Shao et al, 2013;de San Celedonio et al, 2014). In the present study, tillering was most susceptible stage, followed by jointing, booting, and grain filling stages (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In common wheat plants waterlogged at the start of tillering, grain yield losses are mainly caused by a decrease in kernel number per plant (De San Celedonio et al 2014), or in kernel weight per plant (Ghobadi et al 2011), or by a combined reduction in kernel number per plant and the number of culms (Collaku and Harrison 2002). Common wheat tolerance to waterlogging is related to factors such as: i) the duration of the waterlogging event, ii) the crop development stage in which waterlogging occurs, and iii) the sensitivity of the species or variety (Belford 1981;Meyer and Barrs 1988;Brisson et al 2002;Ghobadi and Ghobadi 2010;De San Celedonio et al 2014).…”
mentioning
confidence: 99%